Facile construction of Pt/TiO2/Se/Ni heterostructure for efficient visible-light-driven PEC water splitting - Chen, Ying-Chu; Huang, Yen-Wei; Hsu, Yu-Kuei (Frontiers in Chemistry, 2025)
In this study, a novel Pt/TiO2/Se/Ni heterostructure photocathode was successfully fabricated via a simple and cost-effective method involving galvanic replacement, thermal annealing, and sequential spin-coating processes. Amorphous selenium was first deposited on nickel foil and subsequently transformed into crystalline trigonal Se through thermal treatment. The TiO2 and Pt nanoparticles were then uniformly decorated onto the Se surface to form a hierarchical heterostructure. Structural, morphological, and compositional characterizations using XRD, SEM, Raman spectroscopy, and XPS confirmed the formation of trigonal selenium and the successful deposition of TiO2 and Pt. Optical and photoelectrochemical (PEC) analyses revealed that the crystalline Se exhibited an optimal band gap of 1.89 eV and efficient visible light absorption. The Pt/TiO2/Se photocathode delivered a significantly enhanced photocurrent density of −5 mA cm-2 at −0.3 V vs. Ag/AgCl, which is 1.6 times higher than that of the bare Se electrode. Mott–Schottky and EIS analyses demonstrated an increased carrier density and reduced charge transfer resistance, facilitating efficient charge separation and transfer. These findings highlight the great potential of the Pt/TiO2/Se heterostructure as a high-performance photocathode for solar hydrogen production applications.